Epineural scarring visualization and noninvasive quantification of a severe posttraumatic complication: an experimental magnetic resonance neurography Study - Brunnée, Merle; Aman, Martin; Mayrhofer-Schmid, Maximilian; Fischer, Manuel; Däschler, Simeon C.; Klemm, Tess; Kneser, Ulrich; Karimian-Jazi, Kianush; Breckwoldt, Michael O.; Harhaus-Wähner, Leila; Heiland, Sabine; Bendszus, Martin; et al. (Investigative radiology, 2025)
Peripheral nerve scarring is a severe yet common complication following nerve injury or surgery that can lead to impaired nerve function, including chronic pain and sensory or motor deficits. In this study, we aimed to establish high-resolution magnetic resonance neurography (MRN) to accurately visualize and monitor de novo–formed epineural fibrotic adhesions (EFAs) of the sciatic nerve in a rat nerve injury model.
Gesehen am 11.08.2025